Lymphocyte depletion and subset alteration correlate to renal function in chronic kidney disease patients. (2nd January 2016) - Xiang, Fang-fang; Zhu, Jia-ming; Cao, Xue-sen; Shen, Bo; Zou, Jian-zhou; Liu, Zhong-hua; Zhang, Hao; Teng, Jie; Liu, Hong; Ding, Xiao-qiang
Abstract: Background : It is widely accepted that chronic renal failure is associated with severe alterations of immune system. However, few studies looked into the immune alteration in earlier stage of chronic kidney disease (CKD) patients. To characterize immune defect in CKD patients, we performed lymphocyte subset analysis and explored its relationship to renal function in this population. Methods : 472 CKD patients were enrolled in this study. Lymphocyte subsets (CD19 +, CD3 +, CD3 + CD4 +, CD3 + CD8 +, CD56 + CD16 + ) were determined by flow cytometry. Clinical and laboratory data were collected. Patterns of immune cells in different stages of CKD were compared. Multivariate linear regression was used to evaluate the relationship between lymphocyte subset group and renal function. Correlation analysis was used to assess the relationship between lymphocyte subset and other clinical and laboratory data. Results : Decreased lymphocyte counts occurred long before the end stage of renal disease. Increased NK cell percentage was negatively related to estimated glomerular filtration rate (eGFR) ( r  = −0.259, p <  0.001) while B cell percentage was positively related to eGFR ( r  = 0.249, p <  0.001). Further multivariate linear regression showed increased B cell percentage ( β  = 16.470, 95%CI [1.018–31.922], p =  0.037) and decreased NK cell percentage ( β  = −10.659, 95%CI [−20.063 to −1.254], p =  0.026) were independently correlated with higher eGFR, respectively. Patients with lower NK cell percentage and higher B cell percentage tended to have the best renal function. Conclusions : Lymphocyte depletion and subset alteration occurred during the progress of CKD. Further studies are needed to clarify the role of immune system in CKD and to expand our knowledge about the effect of uremia on the structure and function of immune system.